2023
DOI: 10.7759/cureus.38101
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant Hepatitis A and E Co-infection Leading to Acute Liver Failure: A Case Report

Abstract: Acute liver failure (ALF) is a severe clinical condition with a high mortality rate. Although several factors can cause ALF, viral hepatitis remains one of the leading causes. Hepatitis A virus (HAV) and hepatitis E virus (HEV), which typically cause self-limiting acute disease, are rare but emerging causes of ALF, especially when both viruses infect the same individual. Both of these hepatotropic viruses share an enteric route and are most commonly transmitted through the fecal-oral route. The impact of HAV/H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The five co-infected patients in this study developed coagulopathy, jaundice, and encephalopathy. Similarly, several reports and case studies showed that HAV-HEV coinfection could be complicated by encephalopathy, jaundice, cholecystitis, and fulminant hepatic failure, which could eventually to death [17,64,68].…”
Section: Discussionmentioning
confidence: 91%
“…The five co-infected patients in this study developed coagulopathy, jaundice, and encephalopathy. Similarly, several reports and case studies showed that HAV-HEV coinfection could be complicated by encephalopathy, jaundice, cholecystitis, and fulminant hepatic failure, which could eventually to death [17,64,68].…”
Section: Discussionmentioning
confidence: 91%
“…Although acute infections with the hepatitis A virus in children are self-limited, 0.1% of patients progress to fulminant hepatic failure that spontaneously Z recovers in 40% of cases 6 , 16 . Defining the root cause of ALF is ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Defining the root cause of ALF is ambiguous. Hepatitis A and E account for an enormous percentage of cases worldwide of acute liver failure, with a mortality rate exceeding 50%, especially in developing countries 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang and colleagues identified two mutations in the ORF1 of HEV-1 that enhanced viral replication and may be associated with FHF [ 32 ]. Rarely, HEV can lead to ALF not only in pregnant women but also in elderly patients, patients with leukaemia or coinfection with other hepatotropic viruses [ 33 , 34 , 35 ]. HEV-3 and HEV-4, on the other hand, do not appear to cause fatal infections with fulminant hepatitis in pregnant women, but this has to be confirmed in future studies [ 36 ].…”
Section: Introductionmentioning
confidence: 99%